2015
DOI: 10.4236/epe.2015.710045
|View full text |Cite
|
Sign up to set email alerts
|

Review on People’s Lifestyle and Energy Consumption of Asian Communities: Case Study of Indonesia, Thailand, and China

Abstract: This paper focuses on the residential housing performance and people's lifestyle in terms of energy use. The research has to be continuously study in order to change the Asian people's lifestyle moving toward the low energy consumption. The research began with collecting data by questionnaires which already distributed to some cities of some countries in Asia. In this paper, we conducted review of energy behavior in housing of three different countries, Indonesia, China, and Thailand. Through questionnaire sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…It is known that food availability and food accessibility are the indicators of food security that depict the situation of farm household, while food consumption is the indicator of direct impact of food security, reflected by the quantity and quality of farm household food consumption. The result found that significant relationship was found 78.78 % (Table 2) between household food security, food consumption pattern and exogenous variables (household size, access to food family expenditure, energy consumption (Novianto et al, 2015), and protein consumption (Bahta et al, 2017).…”
Section: Level Of Household Food Securitymentioning
confidence: 98%
“…It is known that food availability and food accessibility are the indicators of food security that depict the situation of farm household, while food consumption is the indicator of direct impact of food security, reflected by the quantity and quality of farm household food consumption. The result found that significant relationship was found 78.78 % (Table 2) between household food security, food consumption pattern and exogenous variables (household size, access to food family expenditure, energy consumption (Novianto et al, 2015), and protein consumption (Bahta et al, 2017).…”
Section: Level Of Household Food Securitymentioning
confidence: 98%
“…Several studies of residential energy consumption have been conducted in Southeast Asia [5][6][7][8][9]. The MECON project investigated ways of increasing energy efficiency among low-income households who have access to grid electricity in the Greater Mekong Subregion (Cambodia, Laos, Myanmar, Thailand, and Vietnam).…”
Section: Introductionmentioning
confidence: 99%
“…The motivation to use PSS could be changed according to the specific needs and focus of residents in Bangkok, and the environmental impacts from the use of PSS may also produce different results from other countries where most consumers own a PW. However, few studies have investigated the environmental impact of the use of PSS and PW in laundry habits in countries in which PW have yet to become widespread, such as Thailand [3,22]. The study aimed to define the use of CL and LS and to clarify the environmental implications of PSS in laundry habits in Bangkok, Thailand.…”
Section: Introductionmentioning
confidence: 99%